Analisis Upaya Perlindungan Tenaga Kesehatan di Puskesmas Cilegon pada Situasi Pandemi Covid-19 - Rosiyana; Adang Bachtiar (NERSMID : Jurnal Keperawatan dan Kebidanan, 2021)
By 1 September 2020, a total of 101 health personnel in Indonesia were reported dead, with the highest mortality ratio compared with other countries (a CFR of 1,36%). A big number of public health centre employees at the city of Cilegon were reported to be infected by COVID-19. The Indonesian Government through the Ministry of Health have issued guidelines regarding the prevention and management of COVID-19 for health personnel. This study was done to obtain a description of how the COVID-19 prevention procedures were implemented for health personnel. This study is qualitative, data was taken with an independent evaluation form , and to further deepen the results an in depth interview which evaluated the relationship between Malcolm Baldridge  components was done. Our research found that 14 out of 66 evaluation aspects were not fulfilled, therefore the Public Health Centre of Cilegon still needs to improve its prevention procedures in order to maintain the health and safety of the health personnel. With the Malcolm Baldridge approach, the categories that had the biggest concern were the category of measurement-analysis  and management of knowledge, leadership, and workforce focus.